Rigorous Solution of Slopes’ Stability considering Hydrostatic Pressure - Chengchao Li; Pengming Jiang; Aizhao Zhou (Complexity)
According to characteristics of soils in failure, a sliding mechanism of slopes in limit state is divided into five parts, for building a slip line field satisfying all possible boundary conditions. An algorithm is built to obtain the rigorous solution approaching upper and lower bound values simultaneously, which satisfies the static boundary and the kinematical boundary based on the slip line field, while stress discontinuity line and velocity discontinuity line are key points. This algorithm is copared with the Spencer method to prove its feasibility with a special example. The variation of rigorous solution, including an ultimate load and a sliding belt the rigid body sliding along rather than a single slip surface for friction-type soils, is achieved considering hydrostatic pressure with soil parameters changing.